Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/medicina59020349
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic Clues of Histopathologically Aggressive Basal Cell Carcinoma Subtypes

Abstract: Background: The group of histopathologically aggressive BCC subtypes includes morpheaform, micronodular, infiltrative and metatypical BCC. Since these tumors are at increased risk of recurring, micrographically controlled surgery is considered the best therapeutic option. Although dermoscopy significantly improves the clinical recognition of BCC, scarce evidence exists on their dermoscopic criteria. Aim: To investigate the dermoscopic characteristics of histopathologically aggressive BCC subtypes. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, follicular criteria and milky red structureless regions were common dermoscopic clues, each noted in 40.7% of cases. The study also found that the percentage of BSC cases with keratin masses (29.6%) was higher than in other aggressive subtypes of Basal Cell Carcinoma (BCC) such as morpheaform, micronodular, infiltrative, and metatypical BCC [24].…”
Section: Dermoscopy Of Bscmentioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, follicular criteria and milky red structureless regions were common dermoscopic clues, each noted in 40.7% of cases. The study also found that the percentage of BSC cases with keratin masses (29.6%) was higher than in other aggressive subtypes of Basal Cell Carcinoma (BCC) such as morpheaform, micronodular, infiltrative, and metatypical BCC [24].…”
Section: Dermoscopy Of Bscmentioning
confidence: 80%
“…In a recent study, Camela et al [24] revealed that arborizing telangiectasias (77.8%), shiny white structures (66.7%), and ulceration (62.9%) are the most frequently observed dermoscopic structures in BSC. Additionally, follicular criteria and milky red structureless regions were common dermoscopic clues, each noted in 40.7% of cases.…”
Section: Dermoscopy Of Bscmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, micronodular BCCs are often difficult to distinguish from superficial and nodular BCCs because they can present as erythematous macules or thin plaques. Dermoscopically, milky red structureless areas (53.8%), arborizing vessels and short fine telangiectasias (53.8% and 50%, respectively), ulceration (46.2%), and blue structure (57.7%) were commonly observed [ 24 ]. Owing to their multifocal nature, these lesions often have subclinical extension and, consequently, higher recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…All tissue slides used at diagnosis were reviewed to determine pathological characteristics, including histological subtypes of BCC, histological grade of SCC, level of invasion, and perineural invasion. Micronodular, infiltrating, sclerosing/morphoeic, and basosquamous patterns were classified as histopathologically aggressive BCC subtypes [20,21]. The histological grade of SCC was divided using a three-level grading system according to several morphologic features of differentiation (nuclear pleomorphism, degree of keratinization) [22].…”
Section: Pathological Evaluationmentioning
confidence: 99%